EKSISTENSI SURAT PEMBERITAHUAN PAJAK DAERAH (SPTPD) DALAM PROSEDUR PERIJINAN USAHA HOTEL DI KABUPATEN SERANG BERDASARKAN SISTEM PERATURAN DAERAH KABUPATEN SERANG NOMOR 5 TAHUN 2010 TENTANG PAJAK DAERAH - , Lalu Farhan Nugraha, S.H., Adrianto Dwi Nugroho, SH.,Adv.,LL.M. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was motivated by the indications of irregularities in the hotel business licensing and tax collection dikabupatn Attack hotel, where the hotel tax SPTPD submitted by the taxpayer is often used formal basic hotel business licensing. The purpose of this study is: 1) To gain clarity about the legality of the implementation of the Regional Income Tax (SPTPD) Taxes on the ballot in Serang associated with Serang Regency Regulation No. 5 of 2010 on Local Taxes